Breaking the Great Chain of Being: A note on the Paris condemnations of 1277, Thomas Aquinas and the proper subject of metaphysics - Robiglio, Andrea A. (Verbum – Analecta Neolatina, 2004)
In the late 13th century Latin west, the problem of the proper subject of metaphysics (a legacy of the Avicenna Latinus) became relevant. Two candidates were open at the time: that of the “ens in quantum ens” as the proper subject of metaphysics, and that of the separate and “most noble substances”. This transition allows for a deeper reading of the Condemnation of 1277. The structure of the Condemnation reveals an intriguing commitment on the part of the condemned articles concerning the separate substances (or angels) and the peculiar neoplatonic ìchain of beingî that was the underpinning of their accounts. Peter Olivi argued against the neoplatonic “chain of being” soon after 1277. Even if this polemic is still neglected in the secondary literature on 1277, Olivi’s interpretation of the state of the debate reinforces the reading of the Paris Condemnation with regard to neoplatonistic chains of being, and the options available for characterizing the proper subject of metaphysics.